Distinct Signaling Requirements for the Establishment of ESC Pluripotency in Late-Stage EpiSCs - Illich, Damir Jacob; Zhang, Miao; Ursu, Andrei; Osorno, Rodrigo; Kim, Kee-Pyo; Yoon, Juyong; Arauzo-Bravo, Marcos J.; Wu, Guangming; Esch, Daniel; Sabour, Davood; Colby, Douglas; Grassme, Kathrin S.; et al. (Cell Reports, 2016)
It has previously been reported that mouse epiblast stem cell (EpiSC) lines comprise heterogeneous cell populations that are functionally equivalent to cells of either early- or late-stage postimplantation development. So far, the establishment of the embryonic stem cell (ESC) pluripotency gene regulatory network through the widely known chemical inhibition of MEK and GSK3beta has been impractical in late-stage EpiSCs. Here, we show that chemical inhibition of casein kinase 1alpha (CK1alpha) induces the conversion of recalcitrant late-stage EpiSCs into ESC pluripotency. CK1alpha inhibition directly results in the simultaneous activation of the WNT signaling pathway, together with inhibition of the TGFbeta/SMAD2 signaling pathway, mediating the rewiring of the gene regulatory network in favor of an ESC-like state. Our findings uncover a molecular mechanism that links CK1alpha to ESC pluripotency through the direct modulation of WNT and TGFbeta signaling.
CRIS-Team Scopus Importer:2020-09-23